2022
DOI: 10.1007/s10151-022-02690-1
|View full text |Cite
|
Sign up to set email alerts
|

Required distal mesorectal resection margin in partial mesorectal excision: a systematic review on distal mesorectal spread

Abstract: Background The required distal margin in partial mesorectal excision (PME) is controversial. The aim of this systematic review was to determine incidence and distance of distal mesorectal spread (DMS). Methods A systematic search was performed using PubMed, Embase and Google Scholar databases. Articles eligible for inclusion were studies reporting on the presence of distal mesorectal spread in patients with rectal cancer who underwent radical resection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, no study has compared the prognostic roles of the two budding types in patients after neoadjuvant therapy for rectal cancer. Recent studies have shown that patients with rectal cancer undergoing radical surgical resection after long-course nCRT still have a 1.2% likelihood of distal rectal mesenteric cancer cell spread, and distal surgical margins of 40 and 30 mm would result in 10% and 32% residual tumors, respectively [ 35 ]. Furthermore, compared to nCRT, patients with TNT and postoperative adjuvant treatment for rectal cancer receive longer cycles of systemic chemotherapy, and this treatment option is more likely to prevent and remove residual cancer cells and occult metastatic lesions in the area where the patient’s primary cancer is resected, thereby diminishing the likelihood of LR and DM.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no study has compared the prognostic roles of the two budding types in patients after neoadjuvant therapy for rectal cancer. Recent studies have shown that patients with rectal cancer undergoing radical surgical resection after long-course nCRT still have a 1.2% likelihood of distal rectal mesenteric cancer cell spread, and distal surgical margins of 40 and 30 mm would result in 10% and 32% residual tumors, respectively [ 35 ]. Furthermore, compared to nCRT, patients with TNT and postoperative adjuvant treatment for rectal cancer receive longer cycles of systemic chemotherapy, and this treatment option is more likely to prevent and remove residual cancer cells and occult metastatic lesions in the area where the patient’s primary cancer is resected, thereby diminishing the likelihood of LR and DM.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a ≤1 mm clear margin width seems to be inadequate in low responders, probably due to the overwhelmingly high risk of residual tumor burden beyond the distal edge of the tumor [ 22 , 23 , 24 ]. Indeed, a distal margin of ≤1 mm in low responders means not only a higher risk of mucosal/submucosal spread of tumor over the resection edge, but also a higher likelihood of incomplete mesorectal excision with possible residual nodal disease [ 25 ], despite similar mean numbers of harvested nodes being observed with close vs. clear margins (14.6 vs. 15.1, p = 0.604). Furthermore, patients treated with nCRT more often had low or ultralow rectal cancer, and coloanal anastomosis was more frequently performed.…”
Section: Discussionmentioning
confidence: 99%